Pengaruh Kepemimpinan, Komitmen Organisasi, Kepuasan Kerja, Dan Balance Scorecard Terhadap Kinerja Karyawan Pt Xyz Di Jakarta - Rizki Oktaviani (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this study are: First, to explore the effect of leadership on employees performance. Second,  to explore the effect of organizational commitment on employees performance. Third, to explore the effect of job satisfaction on employees performance. Fourth, to explore the effect of  balance scorecard on employees performance. Fifth, to explore the effect of leadership, organizational commitment, job satisfaction, and balance scorecard on employees performance. The population of this research are all employees of PT XYZ. This research uses a quantitative approach. The method of data collection is purposive sampling with 175 respondents. Data is collected using a questionnaire. The technique of data analysis used in this study was regression analysis to examine the hypotheses. The results are: (1) leadership has a significant effect on employees performance; (2) organizational commitment no significant effect on employees performance; (3) job satisfaction has a significant effect on employees performance; (4) balance scorecard has a significant effect on employees performance; (5) leadership, organizational commitment, job satisfaction and balance scorecard have a significant effect toward employees performance.